Flexible sigmoidoscopy in colorectal cancer screening: implications of different colonoscopy referral strategies - Niedermaier, Tobias; Hoffmeister, Michael; Brenner, Hermann (European journal of epidemiology, 2018)
Flexible sigmoidoscopy (FS) screening reduces colorectal cancer incidence and mortality. Its potential to detect proximal neoplasms depends on colonoscopy referral. We estimated diagnostic performance of sigmoidoscopy using 12 different referral criteria in detecting colorectal cancer and advanced adenomas. Colonoscopy results from 14,947 participants of screening colonoscopy in Germany were used to derive sensitivity of sigmoidoscopy for colorectal cancer, advanced adenomas (AAs), and any advanced neoplasms in the proximal colon. It was assumed that FS detects the same neoplasms as colonoscopy within its reach and that distal neoplasms would be followed by colonoscopy. In addition, numbers of colonoscopies needed (NCN) to detect one proximal advanced neoplasm were calculated. The most advanced findings during colonoscopy were colorectal cancer in 213 subjects (1.4%), AA in 1539 subjects (10.2%) and non-advanced adenomas in 2988 subjects (19.8%). Without colonoscopy referral, overall sensitivities for any colorectal cancer, advanced adenoma and any advanced neoplasm (proximal or distal) would be 79, 65 and 66%, respectively. These sensitivities could be increased to up to 86, 83 and 84% by the referral strategies investigated. Compared to referral due to advanced adenomas, referral due to non-advanced adenomas would substantially increase the NCN at a modest gain in sensitivity. Sensitivities were higher and NCNs were lower in men than in women for every strategy. In conclusion, colonoscopy referral can substantially increase sensitivity of sigmoidoscopy-based screening, but the gain by referral due to non-advanced adenomas substantially increases NCN compared to referral due to advanced neoplasms only. Major sex differences may call for sex-specific referral strategies.